PEMBUATAN APLIKASI ASESMEN KONSELING BERBASIS NEURO LINGUISTIC PROGRAMMING UNTUK MENINGKATKAN LAYANAN KONSELING GURU BK SMK SE KABUPATEN BLITAR - Utomo, Prabowo Budi; Akhsani, Rafika; Muluk, Muchammad Saiful (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
Based on data from the Central Bureau of Statistics in 2021, there are 32 Vocational High Schools (SMK) with 6 public and 26 private schools spread across Blitar district. In 2023, the number of SMK students in Blitar district recorded in the Basic Education Data was 16,187 students. Meanwhile, the number of counseling teachers at SMKs in Blitar district is 32, resulting in a counseling teacher: student ratio of 1:506. This reality has an impact on the overload of tasks that affect the productivity of counseling services and the achievement of less than optimal performance of Counseling Guidance teachers. The purpose of this Community Service (PkM) activity is to develop an NLP-based counseling assessment system that can be used by SMK Counseling Guidance teachers in Blitar district in carrying out their duties effectively and efficiently in the counseling process and provide training on the use of SILAKON-NLP to SMK Counseling Guidance teachers in Blitar district. After the PkM activities were carried out, a score of 90.60% was obtained for the NLP-based Counseling Assessment Application with the interpretation of Very Feasible, while for training it obtained a score of 87.14% or there were around 24 participants who expressed satisfaction with the training that was held. Based on the achievements obtained, it can be concluded that in the PKM activities carried out, most respondents understand the material presented in this training and most respondents stated that SILAKON-NLP is easy to understand and use and can help their daily tasks / work in terms of counseling services at school. Keywords: Assessment, Counseling, Counseling Guidance teacher, Neuro-Linguistic Programming